The energy spectra of protons and helium measured with the ATIC experiment - Ahn, H. S.; Seo, E. S.; Adams, J. H.; Bashindzhagyan, G.; Batkov, K. E.; Chang, J.; Christl, M.; Fazely, A. R.; Ganel, O.; Gunasingha, R. M.; Guzik, T. G.; Isbert, J.; et al. (Advances in Space Research, 2006)
The Advanced Thin Ionization Calorimeter (ATIC) balloon experiment is designed to investigate the composition and energy spectra of cosmic rays at the highest energies currently accessible by direct measurements, i.e., the region up to 100 TeV. The instrument consists of a silicon matrix for charge measurement, a graphite target (0.75 nuclear interaction length) to induce hadronic interactions, three layers of scintillator strip hodoscopes for triggering and trajectory reconstruction, and a Bismuth Germanate (BGO) crystal calorimeter (18 radiation lengths) to measure particle energies. ATIC has had two successful Long Duration Balloon (LDB) flights from McMurdo, Antarctica: one from 12/28/00 to 01/13/01 and the other from 12/29/02 to 01/18/03. We present the energy spectra of protons and helium extracted from the first flight, over the energy range from 100 GeV to 100 TeV, and compare them with the results from other experiments at both the lower and higher energies. ATIC-1 results do not indicate significant differences in spectral shape between protons and helium over the investigated energy range. © 2005 COSPAR.